Cervical Extradural “En-Plaque” Meningioma - Mariniello, Giuseppe; Briganti, Francesco; De Caro, Maria Laura Del Basso; Maiuri, Francesco (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Objective Spinal meningiomas with concurrent extradural localization and “en-plaque” growth are exceptional, with only five reported cases in the literature. We report another case and discuss the peculiar diagnostic and surgical features of this very unusual pattern of growth.Case report A 74-year-old woman was observed because of a rapidly progressive tetraparesis, more marked in the left arm. Magnetic resonance imaging depicted an inhomogeneously enhancing tumor of the cervical spine, extending from C4 to T1, with diffuse dural enhancement and extension into the left brachial plexus roots. At operation by laminotomy from C4 to C7 a firm posterior extradural tumor arising from the dura was resected; however, the diffusely infiltrated dura could not be removed. Histology was in favor of a transitional meningioma (WHO I). Postoperatively, irradiation to the operative field with 50 Gy was performed. At follow-up, 18 months after surgery, clinical improvement to moderate tetraparesis was evidenced.Conclusions Spinal extradural “en-plaque” meningiomas have been mainly reported in women and at the cervical region, and show extension to many spinal levels as well as diffuse dural infiltration. Preoperatively, they may be differentiated from spinal metastases and lymphomas because of the presence of a “dural tail” sign and calcifications. The surgical resection is mainly limited to the posterior and lateral extradural tumor component, whereas the whole invaded dura is very difficult to resect, mainly in cases with circumferential infiltration. This results in a high rate of tumor recurrence.
Keywords: spinal meningioma; en-plaque meningioma; magnetic resonance imaging; spine